Symptomatic adrenal suppression among children in Canada. Issue 4 (9th November 2016) - Goldbloom, Ellen B; Mokashi, Arati; Cummings, Elizabeth A; Abish, Sharon; Benseler, Susanne M; Huynh, Hien Q; Watson, Wade; Ahmet, Alexandra
Abstract : Background: Adrenal suppression (AS) is an under-recognised side effect of glucocorticoid (GC) use. AS may go undetected until a physiological stress precipitates an adrenal crisis. The incidence of AS has not been established. We sought to estimate the minimum national incidence and presenting features of paediatric symptomatic AS. Methods: Through the established methodology of the Canadian Paediatric Surveillance Program, over 2500 paediatricians were surveyed monthly for 2 years (April 2010–March 2012) to report new cases of symptomatic AS. Results: Forty-six cases of symptomatic AS were confirmed. The estimated annual incidence is 0.35/100 000 children aged 0–18 years (95% CI 0.26 to 0.47). The most common presentations were growth failure (35%), non-specific symptoms (28%) or both (13%). Adrenal crisis occurred in six cases (13%). Thirty-seven children (80%) had received inhaled corticosteroid (ICS) alone or in combination with other GC forms. Many children received high but commonly prescribed doses of ICS. Conclusions: AS is responsible for significant morbidity in children, including susceptibility to adrenal crisis. The minimal estimated incidence reported is for the entire paediatric population and would be much higher in the at-risk group (ie, children treated with GCs). Close monitoring of growth and possible symptoms of AS, which may be non-specific, are important in children on all forms of GC therapy including ICS. To reduce the risk of AS, physicians must be aware of the risk of AS, revisit GC doses frequently and use the lowest effective dose.